2010
DOI: 10.1186/cc8859
|View full text |Cite
|
Sign up to set email alerts
|

The use of a blood conservation device to reduce red blood cell transfusion requirements: a before and after study

Abstract: IntroductionAnaemia and the associated need for packed red blood cell (PRBC) transfusions are common in patients admitted to the intensive care unit (ICU). Among many causes, blood losses from repeated diagnostic tests are contributory.MethodsThis is a before and after study in a medical ICU of a university hospital. We used a closed blood conservation device (Venous Arterial blood Management Protection, VAMP, Edwards Lifesciences, Irvine, CA, USA) to decrease PRBC transfusion requirements. We included all adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 23 publications
1
46
0
1
Order By: Relevance
“…Such waste can be eliminated by returning this blood to the patient, either via three-way stopcock or a commercially available blood-sampling system. Using such a closed system decreases blood loss (109,112) and one before-and-after study also showed reduced amount of blood transfusions (0.07 vs. 0.13 units/patient/day; P ¼ 0.02), and even reduced hospital mortality (30 vs. 53%; P ¼ 0.001) (113).…”
Section: Minimization Of Blood Lossmentioning
confidence: 89%
“…Such waste can be eliminated by returning this blood to the patient, either via three-way stopcock or a commercially available blood-sampling system. Using such a closed system decreases blood loss (109,112) and one before-and-after study also showed reduced amount of blood transfusions (0.07 vs. 0.13 units/patient/day; P ¼ 0.02), and even reduced hospital mortality (30 vs. 53%; P ¼ 0.001) (113).…”
Section: Minimization Of Blood Lossmentioning
confidence: 89%
“…La première étape d'une stratégie d'épargne transfusionnelle est probablement de réduire le vampirisme médical lié aux prélèvements sanguins. Outre une prescription raisonnée des examens biologiques, l'utilisation d'un système de réinjection de la purge sur la ligne artérielle ou de tubes d'examens à volume réduit ou de tubes pédiatriques peuvent permettre de diminuer la spoliation sanguine voire de diminuer le recours à la transfusion de CGR [88][89][90][91]. L'utilisation d'EPO, souvent associée à une supplémenta-tion martiale, a été proposée afin de limiter le recours à la transfusion de CGR en réanimation, sur la base des excellents résultats obtenus chez les patients insuffisants rénaux et d'observations expérimentales d'inhibition de l'apoptose des progéniteurs érythroïdes obtenus chez des patients de réanimation [10].…”
Section: Espoirs Et Déceptions Des Stratégies D'épargne Transfusionnelleunclassified
“…However, the reported effects of blood reduction strategies on transfusion requirements were different between these studies; only Mukhopadhyay et al [9] reported a significant reduction in the amount of transfused packed cells following reduction of iatrogenic blood loss.…”
mentioning
confidence: 97%